Antiangiogenic drugs in combination with seaweed fucoidan: A mechanistic in vitro and in vivo study exploring the VEGF receptor and its downstream signaling molecules in hepatic cancer - Abdollah, Maha R. A.; Ali, Aya A.; Elgohary, Hassnaa H.; Elmazar, Mohamed M. (Frontiers in Pharmacology, 2023)
Hepatocellular carcinoma (HCC) is one of the most common cancers reported worldwide with poor morbidity and high mortality rates. HCC is a very vascular solid tumour as angiogenesis is not only a key driver for tumour progression but also an exciting therapeutic target. Our research investigated the use of fucoidan, a sulfated polysaccharide readily abundant in edible seaweeds commonly consumed in Asian diet due to their extensive health benefits. Fucoidan was reported to possess a strong anti-cancer activity, but its anti-angiogenic potential is still to be fully unraveled. Our research investigated fucoidan in combination with sorafenib (an anti-VEGFR tyrosine kinase inhibitor) and Avastin® (bevacizumab, an anti-VEGF monoclonal antibody) in HCC both in vitro and in vivo. In vitro on HUH-7 cells, fucoidan had a potent synergistic effect when combined with the anti-angiogenic drugs and significantly reduced HUH-7 cell viability in a dose dependent manner. Using the scratch wound assay to test cancer cell motility, sorafenib, A + F (Avastin and fucoidan) or S + F (sorafenib and fucoidan) treated cells consistently showed an unhealed wound and a significantly smaller %wound closure (50%–70%) versus untreated control (91%–100%) (p < 0.05, one-way ANOVA). Using RT-qPCR; fucoidan, sorafenib, A + F and S + F significantly reduced the expression of the pro-angiogenic PI3K/AKT/mTOR and KRAS/BRAF/MAPK pathways by up to 3 folds (p < 0.05, one-way ANOVA versus untreated control). While ELISA results revealed that in fucoidan, sorafenib, A + F and S + F treated cells, the protein levels of caspases 3, 8, and 9 was significantly increased especially in the S + F group showing 40- and 16-times higher caspase 3 and 8 protein levels, respectively (p < 0.05, one-way-ANOVA versus untreated control). Finally, in a DEN-HCC rat model, H&E staining revealed larger sections of apoptosis and necrosis in the tumour nodules of rats treated with the combination therapies and immunohistochemical analysis of the apoptotic marker caspase 3, the proliferation marker Ki67 and the marker for angiogenesis CD34 showed significant improvements when the combination therapies were used. Despite the promising findings reported herein that highlighted a promising chemomodulatory effect of fucoidan when combined with sorafenib and Avastin, further investigations are required to elucidate potential beneficial or adversary interactions between the tested agents.